Dinamika Komunikasi Budaya Antara Mahasiswa Lokal Makassar Dan Mahasiswa Pendatang Di Universitas Muslim Indonesia Sulawesi Selatan - Nur Akbar; Muhammad Zul Iman (CV. SINAR HOWUHOWU, 2026)
This study aims to explore and analyze in depth the forms, dynamics, and adaptation processes of cultural communication between local Makassar students and non-local students at Universitas Muslim Indonesia (UMI), South Sulawesi. Amid massive academic mobility, multicultural higher education institutions such as UMI serve as arenas where diverse ethnic backgrounds, languages, and value systems meet. This study uses a descriptive qualitative method, with data collected through participatory observation, semi-structured in-depth interviews, and documentation studies involving key informants from both local and non-local student groups. The results show that intercultural interaction within the campus environment is inseparable from semantic and psychological barriers in the early phase, such as differences in dialect, intonation, and voice volume that are often misinterpreted as confrontation. However, through meaning negotiation, the optimal use of non-verbal symbols, and a shared collective identity as an Islamic-based academic community, these barriers can be reduced. The adaptation process proceeds dialectically through the stages of stress-adaptation-growth, ultimately establishing communication equilibrium and strengthening cross-cultural solidarity on campus.